Ag-diffusion inhibition mechanism in SiO2-added glass-ceramics for 5G antenna applications. Issue 15 (15th October 2020) - Feng, Kuei-Chih; Chu, Ming-Wei; Ku, Chia-Hao; Chen, Pin-Yi; Tu, Chi-Shun; Chen, Cheng-Sao; Chien, R.R.; Iizuka, Yoshiyuki
Abstract: Glass-ceramics for low-temperature co-fired-ceramic 5G wireless devices exhibit excellent microwave properties. However, silver diffusion and interdiffusion of the electrode decreases the high-frequency conductivity. In this work, the inhibition of the silver diffusion mechanism in CaO-MgO-SiO2 glass-ceramics was investigated. Specimens without SiO2 were found to exhibit both Ag diffusion and Zn, Mg, and Ca interdiffusion. In contrast, samples with SiO2 show much less diffusion and a Ag6 O2 phase at the diffusive boundary layer, indicating that the SiO2 addition inhibits Ag diffusion and interdiffusion. Elemental mapping indicated the presence of a concentration gradient-reaction between the SiO2 particles and the glass-ceramic. This reaction enhances the glass viscosity and inhibits Ag diffusion and interdiffusion. SiO2 -added glass-ceramics co-fired with an Ag electrode show improved 5G-patch-antenna microwave characteristics, with an enhanced conductivity at ~8.2 GHz and a return loss of S11  = -23 dB at ~28.3 GHz.